ANALISIS ISI SURAT KABAR TENTANG ISU KETENAGAKERJAAN DI TINGKAT NASIONAL DAN DIY TAHUN 2012 - , REZA DWI FEBIYANTI, Dr. Sukamdi, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Labor condition in Indonesia, which is not good allow many employment issues happen. Sometimes, news in mass media are not ojective, so that why should be an analysis content of mass media. Ways of the press looked at the issue and how the press to perform its functions can be studied through the Analysis of Media Content . The aims of this research are 1) to understand the real employment issues with in the newspaper , 2) to understand whether there is a difference between national and local newspapers for disclosure of employment issues ,3) to understand whether employment issues are issues that considered important by the newspaper , 4) to understand the spatial and temporal distribution of employment issues in the newspaper . Methods used in this research is content analysis. Data collection techniques used in this research is coding through coding sheet. Data of employment issues that have been collected through coding sheet, then processed using microsoft excel. Cross check between the data sources using triangulation method. Researcher conducted indepth interview to Kompas and Kedaulatan Rakyat editor staff to cross check the result of newspaper data and the existing secondary data. Data result is displayed in the form of frequency tables and graphs based on predefined categories. The results indicate that the existing employment issues in newspapers tend to have in common with the real the employment problems. Employment problems has not become important issues to national and local newspapers (DIY). There is a different perception between national and local newspapers in reviewing employment news . Employment news more likely to appear at the time when approaching labour day and wages setting by government. National newspaper tend to cover employment issues in Jakarta while local newspaper tend to cover local issues of employment.